Analysis and design of the Integrated Sistem Pemantauan Agensi Awam (ISPAAA) - Haddadi, Ali, author; Salwani Mohd. Daud, supervisor; Faculty of Advanced Informatics School (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2014)
Thesis (Sarjana Sains (Kejuruteraan Perisian)) - Universiti Teknologi Malaysia, 2014